Therapeutic and Prophylactic Potential of Morama (Tylosema esculentum): A Review. (21st July 2015) - Chingwaru, Walter; Vidmar, Jerneja; Kapewangolo, Petrina T.; Mazimba, Ofentse; Jackson, Jose
<x xml:space="preserve">Abstract</x> Tylosema esculentum (morama) is a highly valued traditional food and source of medicine for the San and other indigenous populations that inhabit the arid to semi‐arid parts of Southern Africa. Morama beans are a rich source of phenolic acids, flavonoids, certain fatty acids, non‐essential amino acids, certain phytosterols, tannins and minerals. The plant's tuber contains griffonilide, behenic acid and starch. Concoctions of extracts from morama bean, tuber and other local plants are frequently used to treat diarrhoea and digestive disorders by the San and other indigenous populations. Information on composition and bioactivity of phytochemical components of T. esculentum suggests that the polyphenol‐rich extracts of the bean testae and cotyledons have great potential as sources of chemicals that inhibit infectious microorganisms (viral, bacterial and fungal, including drug‐resistant strains), offer protection against certain non‐communicable diseases and promote wound healing and gut health. The potential antinutritional properties of a few morama components are also highlighted. More research is necessary to reveal the full prophylactic and therapeutic potential of the plant against diseases of the current century. Research on domestication and conservation of the plant offers new hope for sustainable utilisation of the plant. Copyright © 2015 John Wiley & Sons, Ltd.